2019
DOI: 10.3389/fmicb.2019.02611
|View full text |Cite
|
Sign up to set email alerts
|

Host Intrinsic and Innate Intracellular Immunity During Herpes Simplex Virus Type 1 (HSV-1) Infection

Abstract: When host cells are invaded by viruses, they deploy multifaceted intracellular defense mechanisms to control infections and limit the damage they may cause. Host intracellular antiviral immunity can be classified into two main branches: (i) intrinsic immunity, an interferon (IFN)-independent antiviral response mediated by constitutively expressed cellular proteins (so-called intrinsic host restriction factors); and (ii) innate immunity, an IFN-dependent antiviral response conferred by IFN-stimulated gene (ISG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 215 publications
(348 reference statements)
0
36
0
2
Order By: Relevance
“…Detection of viral nucleic acid by host pattern recognition receptors (PRRs) plays a critical role in the activation of signalling cascades that lead to the production of pro-inflammatory cytokines, including type-I, II, and III IFNs ( Unterholzner and Almine, 2019 ; Stempel et al, 2019 ; Alandijany, 2019 ). Secretion of IFNs leads to the induction of hundreds of IFN stimulated genes (ISGs) that generate a cellular antiviral state that limits virus propagation and spread.…”
Section: Icp0 Scrambles Innate Immune Pathwaysmentioning
confidence: 99%
“…Detection of viral nucleic acid by host pattern recognition receptors (PRRs) plays a critical role in the activation of signalling cascades that lead to the production of pro-inflammatory cytokines, including type-I, II, and III IFNs ( Unterholzner and Almine, 2019 ; Stempel et al, 2019 ; Alandijany, 2019 ). Secretion of IFNs leads to the induction of hundreds of IFN stimulated genes (ISGs) that generate a cellular antiviral state that limits virus propagation and spread.…”
Section: Icp0 Scrambles Innate Immune Pathwaysmentioning
confidence: 99%
“…Interestingly, whilst DNA viruses typically initiate VRC formation at or in close proximity to PML NBs, many PML NB proteins contribute to the intrinsic antiviral restriction of DNA viruses if their function is not antagonized by the virus. These proteins include PML itself, the transcription corepressor and histone chaperone death domain associated protein 6 (DAXX), transcriptional regulator ATRX, transcription co-regulator Sp100, and E3 SUMO-protein ligase PIAS1 [3,24,[28][29][30][31][32][33][34]. This has led many to questions regarding whether the spatial relationship between VRCs and PML NBs is the result of viral strategies to target these nuclear domains or antiviral strategies that target viral genomes [3,6,24].…”
mentioning
confidence: 99%
“…ICP0 transiently localizes to PML NBs, mediating the proteasome-dependent degradation of PML and Sp100 and the disruption of PML NB through the E3 ubiquitin ligase activity of its really interesting new gene (RING) domain [37][38][39]. In the absence of ICP0, PML and other PML NB proteins act to suppress HSV-1 gene expression and restrict infection, highlighting the intrinsic antiviral function of PML NBs and the requirement of HSV-1 to antagonize this aspect of PML NB function [3,24,[27][28][29]31,40]. The necessity to antagonize the PML NB function appears to be shared by most if not all herpesviruses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The HSV-1 tegument-associated proteins ICP0 and ICP4 are two key factors during HSV-1 replication. Both proteins are not only important modulators of intrinsic and innate immunity (Alandijany, 2019;Tognarelli et al, 2019), but are also crucial during the initiation of the viral gene expression cascade (Guo et al, 2010). On the one hand, it has been suggested that ICP4 might be an L-particle specific viral protein (Szilágyi and Cunningham, 1991;Heilingloh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%